ELT STUDENTS’ PERCEPTIONS TOWARDS WHATSAPP FOR LEARNING ENGLISH DURING THE COVID-19 PANDEMIC - Karimah, Imroatul; Tresnadewi, Sintha; Masduqi, Harits (J-ELLiT (Journal of English Language, Literature, and Teaching), 2022)
The research was conducted to find out the perceptions of ELT students towards the use of WhatsApp as a Mobile-Assisted Language Learning (MALL) device for learning English during the COVID-19 pandemic. The researcher distributed a survey which was filled out by 225 English Language Teaching (ELT) students of Universitas Negeri Malang, Indonesia. The data analysis results show that the students find WhatsApp convenient features due to its connectivity, instant, portability, spontaneity, personalized, and ubiquity. They think that the app is useful for bite-size learning, blended learning, collaborative learning, various learning strategies, learning autonomy, task-based learning, asynchronous and synchronous learning, facilitating interactivity, and for mediating learning. They are also content to use WhatsApp for self-study and improving learning motivation.